2010
DOI: 10.1111/j.1365-3083.2010.02422.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐27 as a Negative Regulator of Human Neutrophil Function

Abstract: Interleukin-27 (IL-27) is a novel cytokine of the IL-6/12 family with a broad range of immune regulation properties, which has been considered as a potential therapeutic agent for immune diseases and cancers. However, little is known about the effect of IL-27 on human neutrophils before its clinical administration. In this study, we investigated the effects of IL-27 on human neutrophil functions including adhesion, reactive oxygen species (ROS)/cytotoxic granule components production, inflammatory cytokines pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 37 publications
3
32
0
Order By: Relevance
“…In addition we found that the chemokine production of endothelial cells upon stimulation with IL-1β or IL-6 was suppressed by IL-27. Moreover, IL-27 has been reported to directly affect adhesion and activation of neutrophils [55].…”
Section: Discussionmentioning
confidence: 99%
“…In addition we found that the chemokine production of endothelial cells upon stimulation with IL-1β or IL-6 was suppressed by IL-27. Moreover, IL-27 has been reported to directly affect adhesion and activation of neutrophils [55].…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of IL-27 functionality has largely come from T cell biology, and its role in the adaptive immune response is well described 1214 . However, the IL-27 receptor complex is also expressed on other immune cell types, including granulocytes 16 and macrophages 17 , indicating that the functional capabilities of IL27 may be even wider and in particular IL27 may play a role in mediating innate immunity. Indeed, IL-27 can impact the function of innate cell subsets, including macrophages 18 , neutrophils 16, 19 , and dendritic cells 2022 .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there are several reports that demonstrated that IL-27 inhibited Th2 and Th17 responses [16, 17]. It is known that IL-27 could suppress neutrophil function to inhibit neutrophil adhesion [18]. It was reported IL-27 is expressed in gingival crevicular fluid of human subjects [19].…”
Section: Introductionmentioning
confidence: 99%